Malay Genome Project (MGP): A need from Islamic perspective - Engku Ahmad Zaki, Engku Alwi; Norazmi, Anas; Zuriani, Yaacob (TextRoad Publication, 2017)
The rapid technological advances have led new hopes in human genome research and have yielded important and informational contents concerning the mapping and sequencing of the entire human genome. Certainly with this powerful medical progress, geneticicsts are able to understand, identify and isolate genes that are responsible for causing more than 4,000 genetic diseases. It has been established that the Malay genome study in Malaysia has been conducted by the Center of Pharmacogenomics (iPROMISE), Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Puncak Alam, Selangor, Malaysia. Henceforth, this fundamental study is an attempt of the researchers to expose the public to the concepts and achievements of the study in Malay genome. Generally, Malay genome projects have succeeded in producing genome databases specifically on the genetic structure of the Malays as well assisting in producing new cures, diagnosing diseases as well as observing its resistance to certain drugs. In addition, some efforts have been made to identify genetic variations and pattern disequilibrium with the disease. Thus, in this intensive study, the researchers intend to explore the genetic ethics with regard to Islamic viewpoints that are seen significant to increase one’s faith. This will later aid in the manipulation of scientific approaches for the benefits of Muslims worldwide.